A phosphorus-bismuth co-doped porous carbon negative electrode material, a preparation method thereof and a sodium ion battery
Patent Information
- Application Number
- CN202611227271.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明提供一种磷铋共掺杂多孔碳负极材料及其制备方法和一种钠离子电池,旨在通过磷、铋协同掺杂与多孔碳限域机制,提供一种兼具高初始库仑效率和优异循环稳定性的复合负极材料,以解决现有钠离子电池负极材料中纯铋合金负极首圈库仑效率过低、充放电过程中体积膨胀导致颗粒粉化和容量剧烈波动,以及纯多孔碳材料亲钠性差、可逆容量低等问题
本发明提供一种磷铋共掺杂多孔碳负极材料及其制备方法,通过磷、铋共掺杂与多孔碳限域机制的协同作用,实现对碳基负极材料的结构和电子的双重优化。其中,磷原子掺杂进入碳晶格,撑开了碳层间距并引入大量结构缺陷,一方面有利于铋的沉积,另一方面碳的结构缺陷和沉积的铋均可提供大量“亲钠”位点,从而吸引钠离子优先在这些点位成核,避免随机、杂乱的沉积,且有利于促进离子/电子的快速传输微观上降低电流密度,使钠的沉积更均匀、致密。铋纳米颗粒均匀限域在三维多孔碳骨架中,不仅作为高容量的合金化储钠中心,还通过其优异的本征电子传导率形成高效的导电网络。多孔碳骨架的物理限域作用有效缓冲了铋在合金化/去合金化过程中的体积膨胀,抑制了颗粒粉化和电极结构崩塌。进一步地,与其他普通多孔碳相比,选用孔径为10~20 nm的介孔碳作为多孔碳,可以为钠离子提供快速传输通道,实现快速充放电,同时介孔材料的高比表面积提供了大量电荷存储位点,可以显著提升电容和电池容量,此外,介孔碳的三维结构可锁住金属颗粒,防止其团聚、枝晶化和失活。
Smart Images

Figure CN123002816A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology and relates to a sodium-ion battery anode material, particularly a phosphorus-bismuth co-doped porous carbon anode material. Background Technology
[0002] After more than 30 years of development, lithium-ion batteries have dominated the portable electronic devices and electric vehicles sectors thanks to their high energy density and mature industrial chain. However, their development still faces many limitations: global lithium resources are limited, making it difficult to simultaneously meet the dual demands of the power battery and energy storage markets; and battery performance degrades significantly at low temperatures, with the risk of thermal runaway. Against this backdrop, sodium-ion batteries have attracted widespread attention due to their abundant resources and controllable costs. Sodium accounts for approximately 2.75% of the Earth's crust, about 400 times more than lithium, and is widely distributed; furthermore, with the continuous maturation of seawater sodium extraction technology, raw material costs are further reduced. Studies have shown that the material cost of sodium-ion batteries is 30% to 40% lower than that of lithium iron phosphate batteries, demonstrating significant economic advantages in large-scale energy storage scenarios.
[0003] Patent application CN122037223A discloses a mechanochemical synthesis method for bismuth-based metal-organic frameworks and its application. By introducing a mixed liquid-phase agent of methanol and N,N-dimethylformamide into a ball milling process, rapid and green synthesis of Bi-MF is achieved under mechanical force. The resulting bismuth / carbon composite material is further obtained through pyrolysis in an inert atmosphere, constructing a three-dimensional porous conductive network in the anode of a sodium-ion battery, effectively improving the material's rate performance and cycle reversibility. However, because this method uses Bi-MOF as a precursor to prepare the composite material through high-temperature pyrolysis, the generation and aggregation of bismuth nanoparticles during pyrolysis are difficult to precisely control. Furthermore, the carbon matrix originates from the pyrolytic carbonization of organic ligands, resulting in a low degree of graphitization and limited intrinsic conductivity. As an alloy-type anode material, bismuth still experiences approximately 250% volume expansion during sodiumification / desodiumification, leading to stress concentration in the electrode structure and insufficient cycle stability.
[0004] Patent application CN122051171A discloses a phosphorus oxide-modified hard carbon anode material, its preparation method, and its application. By introducing a PxOy coating onto the hard carbon surface and generating an inorganic SEI containing metal phosphates in situ during the first charge-discharge process, a stable interfacial protective layer is constructed on the surface of the hard carbon particles based on the surface phosphate enrichment layer. This effectively improves the interfacial stability and ion transport performance of the hard carbon anode in sodium-ion batteries, while also improving the Na+... +The problem lies in the high transport resistance. However, since the modification strategy is limited to surface coating without bulk doping and confined structure control of the carbon matrix, irreversible reaction sites in the hard carbon matrix are difficult to completely eliminate during deep charge and discharge. Furthermore, the PxOy coating mainly acts on interface modification rather than building an internal high-efficiency conductive network, which often results in low initial coulombic efficiency and insufficient electron conduction at high rates. The phosphorus oxide modified hard carbon anode is still accompanied by the continuous dissolution and regeneration of SEI components during cycling, leading to increased interface impedance and capacity decay after long-term cycling, and even local failure of the electrode structure. Moreover, with the increase of charge and discharge rate, its volume expansion and interface side reaction problems will become more serious. Summary of the Invention
[0005] This invention provides a phosphorus-bismuth co-doped porous carbon anode material, its preparation method, and a sodium-ion battery. The aim is to provide a composite anode material with both high initial coulombic efficiency and excellent cycle stability through phosphorus-bismuth co-doping and porous carbon confinement mechanism. This addresses the problems of low initial coulombic efficiency of pure bismuth alloy anodes, particle pulverization and drastic capacity fluctuations caused by volume expansion during charge and discharge, and poor sodium affinity and low reversible capacity of pure porous carbon materials in existing sodium-ion battery anode materials.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a phosphorus-bismuth co-doped porous carbon anode material, comprising the following steps: S1: dissolving a bismuth source and a phosphorus source in an organic solvent to obtain a bismuth source precursor solution and a phosphorus source precursor solution, respectively; dispersing porous carbon in an organic solvent to obtain a porous carbon dispersion; adding the bismuth source precursor solution and the phosphorus source precursor solution dropwise to the porous carbon dispersion solution and mixing them evenly; S2: placing the mixture obtained in step S1 in a sealed environment, heating and stirring; S3: filtering and drying the mixture obtained in step S2, and then calcining it under an inert atmosphere to obtain the phosphorus-bismuth co-doped porous carbon anode material.
[0007] To optimize the above technical solution, the specific measures also include: Further, in step S1, the bismuth source is one or more of bismuth chloride, bismuth nitrate, bismuth sulfate, bismuth acetate, bismuth citrate, and bismuth oxide; the phosphorus source is one or more of trichlorophosphazene and epoxyphenylphosphazene; and the porous carbon is mesoporous carbon.
[0008] Further, in step S1, the mass ratio of the porous carbon, the bismuth source, and the phosphorus source is 10~50∶0.5~2∶0.5~2.
[0009] Further, in step S1, the organic solvent is ethanol; in the bismuth source precursor solution, the phosphorus source precursor solution and the porous carbon dispersion, the mass ratio of the bismuth source, the phosphorus source and the porous carbon to the organic solvent is 1:7~15.
[0010] Further, in step S1, the method for achieving uniform mixing is stirring, with a stirring speed of 0.5~5 Kr / min and a stirring time of 0.5~2 h.
[0011] Further, in step S2, the heating temperature is 40~80 ℃, the stirring speed is 0.5~5 Kr / min, and the heating and stirring time is 1~6 h.
[0012] Furthermore, in step S3, the drying is vacuum drying, with a temperature of 20~100 ℃ and a time of 12~24 h.
[0013] Further, in step S3, the calcination is carried out in a tube furnace, the inert atmosphere is nitrogen or argon, and the calcination process is as follows: first, the temperature is raised to 300-400℃ at a heating rate of 2-5℃ / min and held for 0.5-2 h, then the temperature is raised to 600-900℃ at a heating rate of 2-5℃ / min and held for 1-4 h.
[0014] Secondly, the present invention also provides a phosphorus-bismuth co-doped porous carbon anode material prepared by the above-described preparation method.
[0015] Thirdly, the present invention also provides a sodium-ion battery, including a negative electrode, wherein the negative electrode comprises the above-mentioned phosphorus-bismuth co-doped porous carbon negative electrode material.
[0016] The beneficial effects of this invention are as follows: This invention provides a phosphorus-bismuth co-doped porous carbon anode material and its preparation method. Through the synergistic effect of phosphorus-bismuth co-doping and the confinement mechanism of porous carbon, the structure and electronics of the carbon-based anode material are optimized. Phosphorus atoms doping into the carbon lattice expands the carbon interlayer spacing and introduces numerous structural defects. This is beneficial for bismuth deposition; furthermore, both the carbon structural defects and the deposited bismuth provide numerous sodium-loving sites, attracting sodium ions to preferentially nucleate at these sites, avoiding random and disordered deposition, and promoting rapid ion / electron transport. Microscopically, this reduces current density, resulting in more uniform and dense sodium deposition. Bismuth nanoparticles uniformly confined within the three-dimensional porous carbon framework not only serve as high-capacity alloying sodium storage centers but also form a highly efficient conductive network through their excellent intrinsic electronic conductivity. The physical confinement effect of the porous carbon framework effectively buffers the volume expansion of bismuth during alloying / dealloying, suppressing particle pulverization and electrode structure collapse. Furthermore, compared with other common porous carbons, mesoporous carbon with a pore size of 10~20 nm can provide a fast transport channel for sodium ions, enabling rapid charging and discharging. At the same time, the high specific surface area of mesoporous materials provides a large number of charge storage sites, which can significantly improve capacitance and battery capacity. In addition, the three-dimensional structure of mesoporous carbon can lock metal particles, preventing their agglomeration, dendrite formation and deactivation.
[0017] The phosphorus-bismuth co-doped porous carbon anode material prepared using this invention shows an initial coulombic efficiency increase from less than 10% in the comparative example to approximately 60%. Furthermore, after 80 cycles at a current density of 20 mA / g, its discharge specific capacity remains stable at approximately 60 mAh / g, with a coulombic efficiency approaching 100%. The preparation method of this invention is simple, uses readily available raw materials, and is inexpensive, making it suitable for industrial-scale production and showing promising application prospects in the field of sodium-ion batteries. Attached Figure Description
[0018] Figure 1 These are the X-ray diffraction (XRD) spectra of the negative electrode materials prepared in Example 2, Comparative Example 1, and Comparative Example 2. Figure 2 This is the X-ray photoelectron spectroscopy (XPS) spectrum of the negative electrode material prepared in Example 2; Figure 3 These are the first-cycle constant current charge-discharge (GCD) curves of sodium-ion batteries made with the negative electrode materials of each embodiment and comparative example at a current density of 20 mA / g; Figure 4 This is a comparison graph showing the cycle performance of sodium-ion batteries made with the negative electrode materials of Example 2 and Comparative Example 1 at a current density of 20 mA / g. Figure 5 This is a comparison of electrochemical impedance spectroscopy (EIS) of sodium-ion batteries made from the negative electrode materials of Example 2, Comparative Example 1, and Comparative Example 2. Detailed Implementation
[0019] The present invention will be further described below with reference to specific embodiments.
[0020] Example 1 This embodiment provides a phosphorus-bismuth co-doped porous carbon anode material, the preparation method of which includes the following steps: S1: 25 g of mesoporous carbon was uniformly dispersed in 250 g of anhydrous ethanol to obtain a porous carbon dispersion; 2.5 g of bismuth chloride and 2.5 g of hexachlorocyclotriphosphazene were dissolved in 22.5 g of anhydrous ethanol to obtain bismuth source precursor solution and phosphorus source precursor solution, respectively; the bismuth source precursor solution and phosphorus source precursor solution were added dropwise to the mesoporous carbon dispersion solution and stirred at a speed of 500 r / min for 0.5 h.
[0021] S2: The mixed materials are heated and dispersed in a closed environment at a temperature of 60 ℃, a stirring speed of 500 r / min, and a time of 4 h.
[0022] S3: Filter the heated and stirred mixture and vacuum dry it at 60 °C for 24 h. Place the dried precursor in a crucible and purge it with nitrogen gas at a flow rate of 50-100 mL / min for 30 min in a tube furnace to remove air. Then, raise the temperature to 350 °C at a rate of 3 °C / min and hold for 1 h, then raise it to 800 °C at a rate of 3 °C / min and hold for 2 h. Grind the material into powder after natural cooling to obtain a bismuth-phosphorus co-doped porous carbon anode material, denoted as Bi / P@PC (1∶1∶10).
[0023] Example 2 This embodiment provides a phosphorus-bismuth co-doped porous carbon anode material, the preparation method of which includes the following steps: S1: 25 g of mesoporous carbon was uniformly dispersed in 250 g of anhydrous ethanol to obtain a porous carbon dispersion; 1.25 g of bismuth chloride and 1.25 g of hexachlorocyclotriphosphazene were dissolved in 11.25 g of anhydrous ethanol to obtain bismuth source precursor solution and phosphorus source precursor solution, respectively; the bismuth source precursor solution and phosphorus source precursor solution were added dropwise to the mesoporous carbon dispersion solution and stirred at a speed of 500 r / min for 0.5 h.
[0024] S2: The mixed materials are heated and dispersed in a closed environment at a temperature of 60 ℃, a stirring speed of 500 r / min, and a time of 4 h.
[0025] S3: Filter the heated and stirred mixture and vacuum dry it at 60 °C for 24 h. Place the dried precursor in a crucible and purge it with nitrogen gas at a flow rate of 50-100 mL / min for 30 min in a tube furnace to remove air. Then, raise the temperature to 350 °C at a rate of 5 °C / min and hold for 45 min, then raise it to 750 °C at a rate of 5 °C / min and hold for 1.5 h. Grind the naturally cooled material into powder to obtain a bismuth-phosphorus co-doped porous carbon anode material, denoted as Bi / P@PC (1∶1∶20).
[0026] Example 3 This embodiment provides a phosphorus-bismuth co-doped porous carbon anode material, the preparation method of which includes the following steps: S1: 25 g of mesoporous carbon was uniformly dispersed in 250 g of anhydrous ethanol to obtain a porous carbon dispersion; 0.625 g of bismuth chloride and 0.625 g of hexachlorocyclotriphosphazene were dissolved in 5.625 g of anhydrous ethanol to obtain bismuth source precursor solution and phosphorus source precursor solution, respectively; the bismuth source precursor solution and phosphorus source precursor solution were added dropwise to the mesoporous carbon dispersion and stirred at a speed of 500 r / min for 0.5 h.
[0027] S2: The mixed materials are heated and dispersed in a closed environment at a temperature of 60 ℃, a stirring speed of 500 r / min, and a time of 4 h.
[0028] S3: Filter the heated and stirred mixture and vacuum dry it at 60 °C for 24 h. Place the dried precursor in a crucible and purge it with nitrogen gas at a flow rate of 50-100 mL / min for 30 min in a tube furnace to remove air. Then, raise the temperature to 350 °C at a rate of 5 °C / min and hold for 45 min, then raise it to 750 °C at a rate of 5 °C / min and hold for 1.5 h. Grind the naturally cooled material into powder to obtain a bismuth-phosphorus co-doped porous carbon anode material, denoted as Bi / P@PC (1∶1∶40).
[0029] Comparative Example 1 This comparative example provides a negative electrode material, the preparation method of which includes the following steps: S1: 25 g of mesoporous carbon was uniformly dispersed in 250 g of anhydrous ethanol to obtain a porous carbon dispersion; 2.5 g of bismuth chloride was dissolved in 22.5 g of anhydrous ethanol to obtain a bismuth source precursor solution; the bismuth source precursor solution was added dropwise to the mesoporous carbon dispersion solution and stirred at a speed of 500 r / min for 0.5 h.
[0030] S2: The mixed materials are heated and dispersed in a closed environment at a temperature of 60 ℃, a stirring speed of 500 r / min, and a time of 4 h.
[0031] S3: Filter the heated and stirred mixture and vacuum dry it at 60 °C for 24 h. Place the dried precursor in a crucible and purge it with nitrogen gas at a flow rate of 50-100 mL / min for 30 min in a tube furnace to remove air. Then, raise the temperature to 350 °C at a rate of 5 °C / min and hold for 45 min, then raise it to 750 °C at a rate of 5 °C / min and hold for 1.5 h. Grind the naturally cooled material into powder to obtain a bismuth-phosphorus co-doped porous carbon anode material, denoted as Bi@PC (1:10).
[0032] Comparative Example 2 This embodiment provides a negative electrode material, the preparation method of which includes the following steps: S1: 25 g of mesoporous carbon was uniformly dispersed in 250 g of anhydrous ethanol to obtain a porous carbon dispersion; 2.5 g of hexachlorocyclotriphosphazene was dissolved in 22.5 g of anhydrous ethanol to obtain a phosphorus source precursor solution; the phosphorus source precursor solution was added dropwise to the mesoporous carbon dispersion solution and stirred at a speed of 500 r / min for 0.5 h.
[0033] S2: The mixed materials are heated and dispersed in a closed environment at a temperature of 60 ℃, a stirring speed of 500 r / min, and a time of 4 h.
[0034] S3: Filter the heated and stirred mixture and vacuum dry it at 60 °C for 24 h. Place the dried precursor in a crucible and purge it with nitrogen gas at a flow rate of 50-100 mL / min for 30 min in a tube furnace to remove air. Then, raise the temperature to 350 °C at a rate of 5 °C / min and hold for 45 min, then raise it to 750 °C at a rate of 5 °C / min and hold for 1.5 h. Grind the naturally cooled material into powder to obtain a phosphorus-bismuth co-doped porous carbon anode material, denoted as P@PC (1:10).
[0035] The XRD patterns of the negative electrode materials prepared in Example 2, Comparative Example 1, and Comparative Example 2 are shown below. Figure 1 As shown, the XPS spectrum of the negative electrode material prepared in Example 2 is as follows. Figure 2 As shown.
[0036] Sodium-ion batteries were fabricated using the negative electrode materials from each embodiment and comparative example, and battery tests were conducted.
[0037] The manufacturing process of sodium-ion batteries includes the preparation of negative electrode sheets and battery assembly.
[0038] The preparation method of the negative electrode includes the following steps: T1: Provide calcined negative electrode material powder and 20 mg / ml NMP solution of binder PVDF, with a mass ratio of negative electrode material powder to binder PVDF of 8:2.
[0039] T2: Place the weighed negative electrode material powder and the NMP solution of binder PVDF into a mortar and grind until fine to obtain a negative electrode material slurry.
[0040] T3: Apply the negative electrode material slurry evenly onto the aluminum foil current collector using a coating machine, controlling the coating thickness to be 5 μm.
[0041] T4: Place the coated wet negative electrode sheet into a vacuum drying oven at 80 ℃ and dry for 2 h.
[0042] T5: Cut the dried negative electrode sheet into small round pieces with a diameter of 16 mm, and then compress them using a tablet press at 100 kg / cm². 2 The negative electrode sheet is produced by pressing it under pressure.
[0043] Battery assembly includes the following steps: A1: Select qualified electrode sheets and weigh them using a high-precision balance. Weigh each sheet three times and take the average value.
[0044] A2: Place the positive electrode shell flat on an insulated platform, place the test electrode in the center of the positive electrode shell, add a drop of electrolyte using a pipette to wet the surface of the test electrode, place the diaphragm on the upper layer of the test electrode using insulated tweezers, with the active material side of the test electrode in contact with the diaphragm, add an appropriate amount of electrolyte to the surface of the diaphragm using a pipette, place the sodium sheet on the upper layer of the diaphragm using insulated tweezers, and then place the gasket, spring, and negative electrode shell on the upper layer of the sodium sheet in sequence.
[0045] A3: Using insulated tweezers, place the button cell battery with the negative terminal facing up on the button cell sealing machine mold, and adjust the pressure to 50 kg / cm². 2 Press for 5 seconds to complete the assembly of the button cell. Remove it with insulated tweezers, observe whether the appearance is complete, and wipe it clean with a paper towel.
[0046] Battery testing includes constant current charge-discharge testing, cycle performance testing, and EIS testing.
[0047] Batteries made from the negative electrode materials of each embodiment and comparative example were subjected to constant current charge-discharge tests at a current density of 20 mA / g. The GCD curves are shown below. Figure 3As shown in the results, the test results show that co-doped porous carbon with bismuth phosphorus significantly improves the initial coulombic efficiency, increasing it from less than 10% in the comparative example to approximately 60%. Furthermore, with the increase of bismuth phosphorus doping, the initial coulombic efficiency shows a trend of first increasing and then decreasing, with Bi / P@PC (1∶1∶20) in Example 2 showing the best effect.
[0048] The batteries made from the negative electrode materials of Example 2 and Comparative Example 1 were subjected to cycle performance tests at a current density of 20 mA / g, and the results are as follows: Figure 4 As shown in the figure. The test results show that the discharge specific capacity and cycle stability of Bi / P@PC (1∶1∶20) in Example 2 are better than those of Bi@PC (1∶10) in Comparative Example 1.
[0049] The batteries made from the negative electrode materials of Example 2 and Comparative Example 1 were subjected to EIS testing, and the results are as follows: Figure 5 As shown in the figure, the test results show that compared with single-element doping of phosphorus and bismuth, the impedance of phosphorus-bismuth co-doped porous carbon is lower, indicating that the synergistic effect of phosphorus-bismuth co-doping can significantly reduce the charge transfer impedance of the material and greatly improve its electrochemical performance.
[0050] In this invention, unless otherwise stated, scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. Furthermore, the reagents, materials, and procedures used herein are all widely used in the relevant fields.
[0051] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a phosphorus-bismuth co-doped porous carbon anode material, characterized in that: Includes the following steps: S1: Dissolve bismuth source and phosphorus source in organic solvent to obtain bismuth source precursor solution and phosphorus source precursor solution respectively; disperse porous carbon in organic solvent to obtain porous carbon dispersion; add the bismuth source precursor solution and the phosphorus source precursor solution dropwise to the porous carbon dispersion and mix evenly; S2: Place the mixture obtained in step S1 in a sealed environment, heat and stir; S3: The mixture obtained in step S2 is filtered and dried, and then calcined under an inert atmosphere to obtain the phosphorus-bismuth co-doped porous carbon anode material.
2. The method for preparing the phosphorus-bismuth co-doped porous carbon anode material according to claim 1, characterized in that: In step S1, the bismuth source is one or more of bismuth chloride, bismuth nitrate, bismuth sulfate, bismuth acetate, bismuth citrate, and bismuth oxide. The phosphorus source is one or more of trichlorophosphazene and epoxy phenylphosphazene; The porous carbon is mesoporous carbon.
3. The method for preparing the phosphorus-bismuth co-doped porous carbon anode material according to claim 1, characterized in that: In step S1, the mass ratio of the porous carbon, the bismuth source, and the phosphorus source is 10~50:0.5~2:0.5~2.
4. The method for preparing the phosphorus-bismuth co-doped porous carbon anode material according to claim 1, characterized in that: In step S1, the organic solvent is ethanol; In the bismuth source precursor solution, the phosphorus source precursor solution, and the porous carbon dispersion, the mass ratio of the bismuth source, the phosphorus source, and the porous carbon to the organic solvent is 1:7~15.
5. The method for preparing the phosphorus-bismuth co-doped porous carbon anode material according to claim 1, characterized in that: In step S1, the method for achieving uniform mixing is stirring, with a stirring speed of 0.5~5 Kr / min and a stirring time of 0.5~2 h.
6. The method for preparing the phosphorus-bismuth co-doped porous carbon anode material according to claim 1, characterized in that: In step S2, the heating temperature is 40~80 ℃, the stirring speed is 0.5~5 Kr / min, and the heating and stirring time is 1~6 h.
7. The method for preparing the phosphorus-bismuth co-doped porous carbon anode material according to claim 1, characterized in that: In step S3, the drying is vacuum drying, with a temperature of 20~100 ℃ and a time of 12~24 h.
8. The method for preparing the phosphorus-bismuth co-doped porous carbon anode material according to claim 1, characterized in that: In step S3, the calcination is carried out in a tube furnace, the inert atmosphere is nitrogen or argon, and the calcination process is as follows: first, the temperature is raised to 300-400 ℃ at a heating rate of 2-5 ℃ / min and held for 0.5-2 h, then the temperature is raised to 600-900 ℃ at a heating rate of 2-5 ℃ / min and held for 1-4 h.
9. The phosphorus-bismuth co-doped porous carbon anode material prepared by the preparation method according to any one of claims 1 to 8.
10. A sodium-ion battery, comprising a negative electrode, characterized in that: The negative electrode comprises the phosphorus-bismuth co-doped porous carbon negative electrode material as described in claim 9.
Citation Information
Patent Citations
Mechano-chemical synthesis method of bismuth-based metal organic framework and application of mechano-chemical synthesis method
CN122037223A
Phosphorus oxide modified hard carbon negative electrode material and preparation method and application thereof
CN122051171A
